Beyond 9/11: Poetics of Transcultural Agency in Contemporary Ethnic American Poetry (Altre Modernità, 2011)
In a post-postmodern world void of exclusive identities, limited localities or hindering cultural borders, and in a period of rapid globalization, massive flows of transmigration, and increasing creation of multinationals, the future of mankind should be envisioned as a shared mission accomplished only through negotiation and reconciliation of contradictory cultural experiences. Yet, moving beyond the entrenched boundaries of national space and overcoming the American-third world mutual hatred and distrust – engrained after the 9/11 terrorist attacks on the Twin Towers and America’s war on terrorism – still requires a considerable leap of imagination. Investigating such alternative imagination – which transgresses the narrow borders of place, time and identity, recognizes the dramatic change in the politics of place, understands how there has been both merged and emerged in the characterization of here, views the future as a transcultural treaty that needs to be peacefully negotiated, accepts the limitless boundaries of self-consciousness, and perceives the potentials inherent in the complex interaction and interruption of the other – is the main aim of this paper.
Keywords: postmodernism; post-postmodernism; Naomi Shihab Nye; Li-Young Lee; Transcultural Agency; Ethnic American Poetry